Analisis Analisis Pengelolaan Aset di Rumah Sakit Milik TNI Angkatan Darat (Studi Kasus: Rumah Sakit Bhakti Wira Tamtama Semarang) - yuniarso, yasinda caesar; astuti, puji; ., Sulistyowati (Journal of Politic and Government Studies, 2018)
The hospital is one of the government-owned or private service agencies intended toassist the society to fill the needs of health sector. Nowadays, hospitals keep to develop to meetmarket demands and also answer the need for public awareness about health. One of the thingsthat can be done is to use management one of them is physical assets management. The assetmanagement used so that the asset can provide the highest benefit for the company and thegovernment because the asset is an important part in achieving the goal of the asset owner.The methods in this study using a qualitative approach. Informant in this research is staffof the Hospital of Tk. III Bhakti Wira Tamtama Semarang. Furthermore, the object of this researchis abou the policy, assets, management in the physical assets of Tk Hospital. III Bhakti WiraTamtama Semarang. Data collection is done by interview.The results prove that the physical assets management at Tk Hospital. III Bhakti WiraTamtama Semarang is managed by 3 different task units in each of its divisions, namely URDAL(Internal Affairs), URJANGMED (Medical Supporting Affairs), ULP (Procurement Unit), theseare aimed to achieve the target. While the obstacles that the management of physical assets at TkHospital. III Bhakti Wira Tamtama Semarang is an obstacle to funding, the process that too long,and disrupted development, and a lot of old buildings.The suggestion given by author to Hospital of Tk. III Bhakti Wira Tamtama Semarangin managing the management of physical assets is to prioritize which assets need to be bought orrepaired, by shortening the flow of procurement, and create a safe limit when within the limits ofimprovement.Keyword: Management, Physical Assets